Single and combined strategies for mesenchymal stem cell exosomes alleviate liver fibrosis: a systematic review and meta-analysis of preclinical animal models - Zhou, Xiaolei; Xu, Yan; Wang, Xuesong; Lu, Wenming; Tang, Xingkun; Jin, Yu; Ye, Junsong (Frontiers in Pharmacology, 2024)
Background The efficacy of MSCs in treating liver fibrosis has been supported by various clinical studies. However, stem cell transplantation is limited in clinical application due to its low survival rate, low liver implantation rate, and possible carcinogenicity. Recently, there has been increasing interest in the use of MSC-exos due to their widespread availability, low immunogenicity, and non-carcinogenic properties. Numerous studies have demonstrated the potential of MSC-exos in treating liver fibrosis and preventing progression to end-stage liver disease. Objective This study aimed to systematically investigate the efficacy of MSC-exos single administration for the treatment of hepatic fibrosis and the combined advantages of MSC-exos in combination with drugs therapy (MSC-exos-Drugs). Methods Data sources included PubMed, Web of Science, Embase, and the Cochrane Library, which were built up to 2024 January. The PICOS principle was used to screen the literature, and the quality of the literature was evaluated to assess the risk of bias. Finally, the data from each study’s outcome indicators were extracted for a combined analysis. Results After screening, a total of 18 papers(19 studies) were included, of which 12 involved the MSC-exos single administration for the treatment of liver fibrosis and 6 involved the MSC-exos- drugs for the treatment of liver fibrosis. Pooled analysis revealed that MSC-exos significantly improved liver function, promoted the repair of damaged liver tissue, and slowed the progression of hepatic fibrosis and that MSC-exos-Drugs were more efficacious than MSC-exos single administration. (Fig 1) Subgroup analyses revealed that the use of AD-MSC-exos resulted in more consistent and significant efficacy when MSC-exos was used to treat hepatic fibrosis. For MSC-exos-Drugs, a more stable end result is obtained by kit extraction. Similarly, infusion through the abdominal cavity is more effective. Conclusions The results suggest that MSC-exos can effectively treat liver fibrosis and that MSC-exos-Drugs is more effective than MSC-exos single administration. Although the results of the subgroup analyses provide recommendations for clinical treatment, a large number of high-quality experimental validations are still needed.